Insulin-like growth factor binding protein 2 in bipolar disorder: An expression study in peripheral tissues. (17th November 2018) - Milanesi, Elena; Zanardini, Roberta; Rosso, Gianluca; Maina, Giuseppe; Barbon, Alessandro; Mora, Cristina; Minelli, Alessandra; Gennarelli, Massimo; Bocchio-Chiavetto, Luisella
Abstract: Objectives: Insulin-like growth factor binding protein 2 (IGFBP2) is a member of the family of high-affinity binding proteins (IGFBP1–6) and appears to play a governing role in insulin-like growth factor (IGF) regulation in the central nervous system. This study aimed to investigate the putative involvement of IGFBP2 in mood disorder pathogenesis by measuring its expression levels in patient peripheral tissues. Methods: IGFBP2 protein and mRNA levels were measured in the serum of 93 controls, 41 bipolar disorder (BD) and 43 major depressive disorder (MDD) patients and in the skin fibroblasts from 15 controls, 12 BD and 23 MDD patients. Results: The results indicated reduced expression of IGFBP2 in both tissues of BD patients, whereas no difference was found in MDD patients compared with controls. Conclusions: Our findings in peripheral tissues are consistent with previous results in the brain and support a downregulation of IGFBP2 expression that is specific for BD, suggesting a role for this protein in the alterations in neurodevelopment and neuroprotection observed in the disorder. Further studies in independent and larger cohorts are warranted to confirm the involvement of IGFBP2 in BD.